PENGARUH PENGGUNAAN APLIKASI SIMANDAI TERHADAP MINAT KUNJUNGAN PASIEN (Tinjauan pada RSUD H. Abdul Aziz Marabahan) - Wianda Dewi Puspitasari; Ika Kusuma Wardani; Renie Kumala Dewi; Isnur Hatta; Irham Taufiqurrahman (Dentin, 2026)
Background: According to the 2023 Indonesian Health Survey (SKI), hospitals are the least utilized healthcare facilities. RSUD H. Abdul Aziz Marabahan is a healthcare facility located in Barito Kuala Regency, South Kalimantan. Based on visit data, there were 27,794 patients in 2023 and 20,394 patients in the first half of 2024. This may lead to irregular queues, causing patients to feel dissatisfied and reluctant to visit the hospital. To ensure better queue management, RSUD H. Abdul Aziz Marabahan launched an online registration application called SIMANDAI. To determine whether SIMANDAI is associated with improving user satisfaction and increasing the interest in visiting, an analysis using the End User Computing Satisfaction (EUCS) method is needed. Purpose: To analyse the relationship between the use of the SIMANDAI application and the community’s interest in visiting RSUD H. Abdul Aziz Marabahan. Method: This study is an analytical observational study with a cross-sectional approach. The study population consists of patients at RSUD H. Abdul Aziz Marabahan who use the SIMANDAI application and have received treatment. Results: The Spearman test results show that the content, format, and ease of use dimensions have an effect on visit intention, while the accuracy and timeliness dimensions have no effect on visit intention. Conclusion: Improving the EUCS elements and appropriately promoting the application can increase user satisfaction and the public’s interest in visiting.Keywords : EUCS, Healthcare facility, SIMANDAI, Visit intention